High school to university transitional challenges in English medium instruction in Japan. (December 2020) - Aizawa, Ikuya; Rose, Heath
Abstract: Despite the rapid expansion of English-medium instruction (EMI) at higher education institutions around the world, little research has explored the language-related challenges faced by students when entering an EMI university from a first language (L1) medium high school. This study identifies challenges posed by the school–university transition encountered by L1 Japanese undergraduates who study academic subjects through English at a university in Tokyo. 103 students from various academic disciplines completed questionnaires on academic English challenges in addition to receptive and productive academic vocabulary size tests as a measure of their linguistic preparedness for academic study in English. Semi-structured interviews were subsequently conducted with 20 students. Results show that students who attended Japanese medium high schools where English language classes were taught through English obtained a larger academic vocabulary size and encountered fewer linguistic challenges adjusting to English-medium learning than their counterparts who had studied English through Japanese. This suggests that even 'soft-EMI' high school experiences may lead to an easier transition to university-level EMI contexts. Based on the findings, implications are discussed in terms of the design of EAP (English for Academic Purposes) curricula with a specific focus on vocabulary learning for EMI university students across a range of English language levels.